The Role of Hybrid Cu–Ag Nanoparticles in Modifying Blood Flow Through Narrowed Arteries - Bodke, Nitin Sadashiv; Fernandes, Ignatius (Communications in Mathematics and Applications, 2025)
Blood flow in stenosed human arteries in the presence of hybrid Copper-Silver (Cu–Ag) nanoparticles is studied. The study investigates the influence of copper (Cu) nanoparticles and Cu–Ag hybrid nanoparticles on velocity profiles, flow rate and resistive impedance to blood flow in abnormally narrowed arteries due to stenosis. A laminar unsteady blood flow is considered through a cylindrical tube depicting blood flow in an artery affected by stenosis. Flow parameters are assumed to match the physical properties of the blood flow. Finite difference method is employed to discretize the governing equations and simulation is carried out using MATLAB. The presence of hybrid nanoparticles is observed to have significant influence on velocity, flow rate and impedance to blood flow.
Keywords: Hybrid nanoparticles; Stenosed arteries; Copper-Silver nanoparticles